From Private Debt to Public Shame: Legal Intervention in the Social Consequences of Digital Lending Practices in Indonesia - Fadhel Arjuna Adinda; Rosyidi Hamzah (The Indonesian Journal of Legal Intervention in Social Problems, 2026)
The expansion of digital lending in Indonesia has transformed debt from a predominantly private financial relationship into a potential source of public social pressure. Borrowers may experience harassment, disclosure of personal information, contact with relatives or colleagues, and public shaming when repayment difficulties occur. These practices demonstrate that digital lending can generate social harms that extend beyond contractual disputes and financial loss. This article examines how legal intervention can address the social consequences of abusive digital lending practices in Indonesia. Using a socio-legal approach, the study analyzes the interaction between consumer protection, personal data protection, financial regulation, and the social dynamics of debt collection. The article argues that conventional legal responses focused on contractual obligations and financial compliance are inadequate when debt collection produces humiliation, reputational damage, and social exclusion. Its principal contribution is to reposition abusive debt collection as a broader social and legal problem rather than merely a financial dispute. The study proposes an integrated model of legal intervention combining regulatory enforcement, data protection, accessible complaint mechanisms, and stronger safeguards for vulnerable borrowers, thereby connecting financial regulation with the protection of human dignity in digital society.